Innovative application of optical fiber sensing technology for monitoring stope support pressure distribution in similar model tests - Li, Chao; Zhang, Jialin; Chen, Yu; Hou, Yabin; Shi, Yong; Qu, Yinghao; Yuan, Qiang; Zhang, Mingtian (Frontiers in Earth Science, 2025)
In order to explore the support pressure distribution law in the coal and rock mass around the stope and rock masses under an extremely thick conglomerate layer and evaluate the feasibility of different monitoring techniques, the study established the geometric size of a similar physical model as 3.6 m (length) × 2.0 m (width) × 2.0 m (height) in the laboratory. The test used pulse pre-pumped Brillouin optical time domain analysis (PPP-BOTDA) and pressure sensor technology to monitor distribution law. We placed pressure sensors and sensing elements at the bottom plate of the model to simulate the support pressure distribution around the stope under the thick conglomerate layer. And used theoretical calculations and numerical simulations to conduct comparative analysis. The test results showed that the distributed optical fiber support pressure test system can be used to characterize the variation law of support pressure in the model test. Compared with the pressure sensor, it had a good corresponding relationship. Both of them were basically consistent with the theoretical calculation results and simulation. The optical fiber test had the advantages of high precision and strong anti-interference ability, which were not available in the electric sensor. It provided a new idea for the support pressure test of the model experiment.